Test-driven development in Swift : compile better code with XCTest and TDD - Lodi, Gio (Apress, 2021)
Leverage Swift to practice effective and efficient test-driven development (TDD) methodology. Software testing and TDD are evergreen programming concepts yet Swift developers haven't widely adopted them. What's needed is a clear roadmap to learn and adopt TDD in the Swift world. Over the past years, Apple has invested in XCTest and Xcode's testing infrastructure, making testing a new top priority in their ecosystem. Open-source libraries such as Quick and Nimble have also reached maturity. The tools are there. This book will show you how to wield them. TDD has much more to offer than catching bugs. With this book, you'll learn a philosophy for building software. TDD enables engineers to solve problems incrementally, writing only as much code as necessary. By decomposing big problems into small steps, you can move along at a fast pace, always making visible progress. Participate in the test-driven development journey by building a real iOS application and incorporating new concepts through each chapter. The book's concepts will emerge as you figure out ways to use tests to drive the solutions to the problems of each chapter. Through the TDD of a single application, you'll be introduced to all the staples and advanced concepts of the craft, understand the trade offs each technique offers, and review an iterative process of software development. Test-Driven Development in Swift provides the path for a highly efficient way to make amazing apps. You will: Write tests that are easy to maintain Look after an ever-growing test suite Build a testing vocabulary that can be applied outside the Swift world See how Swift programming enhances the TDD flow seen in dynamic languages Discover how compiler errors can provide the same helpful guidance as failing tests do.